Comparative Efficacy of Herbal vs Fluoride Toothpastes in Reducing Plaque Index and Gingival Bleeding - Usman Mahmood, Farzana Memon, Sadaf Raffi, Mian Farrukh Imran, Syed Shabir Hussain Shah, Fakeha Zahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dental plaque and gingival inflammation are key etiological factors in the progression of periodontal diseases. While fluoride-based toothpastes are widely used for their anti-caries benefits, their role in controlling gingivitis is limited. Herbal formulations containing neem and clove have shown promising antiplaque and anti-inflammatory effects, but robust clinical comparisons with fluoride toothpastes remain scarce. Objective: To compare the efficacy of a neem–clove herbal toothpaste with a conventional fluoride toothpaste in reducing plaque index (PI) and gingival bleeding index (GBI) over an 8-week period in adults with mild to moderate gingivitis. Methods: A randomized, examiner-blinded, parallel-arm comparative clinical study was conducted involving 70 systemically healthy adults aged 18–65. Participants were randomly assigned to use either a herbal toothpaste containing standardized neem and clove extracts (n = 35) or a conventional fluoride toothpaste (1,450 ppm sodium fluoride, n = 35). Clinical parameters, including PI and GBI, were recorded at baseline, Week 4, and Week 8 by a calibrated examiner using standard indices. Compliance and safety were monitored throughout the study. Results: Both groups demonstrated significant reductions in PI and GBI from baseline to Week 8 (p < 0.001). However, the herbal group showed statistically greater reductions in mean PI at Week 4 (1.48 ± 0.34 vs. 1.57 ± 0.36; p = 0.042) and Week 8 (0.92 ± 0.30 vs. 1.03 ± 0.33; p = 0.028). Similarly, GBI scores were significantly lower in the herbal group at both Week 4 (30.6% ± 5.2% vs. 32.5% ± 5.5%; p = 0.037) and Week 8 (19.7% ± 4.6% vs. 22.3% ± 5.0%; p = 0.025). Compliance exceeded 90% in both groups, and no serious adverse events were reported. Conclusion: The neem–clove herbal toothpaste demonstrated superior efficacy in reducing plaque and gingival bleeding compared to a fluoride toothpaste over 8 weeks. The findings support the use of standardized herbal formulations as an effective and safe alternative for managing plaque-induced gingivitis. Keywords: Herbal toothpaste, fluoride toothpaste, gingivitis, plaque index, gingival bleeding index, neem, clove, oral hygiene, clinical trial